Novel conformational isomerism in a six-coordinate silver(i) complex of a sexadentate macrocycle with an 'N3S3' donor set - Bin, Sidik Silong; Kildea, John D.; White, Allan H. (CSIRO Publishing, 1989)
The synthesis and structural characterization of the condensation product formed by a template reaction of 2, 6-diacetylpyridine and 3, 6, 9-trithiaundecane-1, 11-diamine about silver(1) (as perchlorate) are described. Crystals are monoclinic, C2/c, a 27.114(10), b 7.546(5), c 22.137(10) Å, β 105.35(3)°, Z=8×[AgL]+(ClO4)- (L = C17H25N3S3). R was 0.057 for 2372 'observed' reflections. The six-coordinate silver(l) atom lies in a novel environment comprised of a mer-triaza moiety derived from 2, 6-diacetylpyridine [Ag-N, 2.422(8) (central), 2.538(8), 2.546(9) Å (distal)] and a fac-trithia moiety straddling its plane [Ag-S, 2.603(6) (central), 2-815(4), 2.881(3) Å (distal)]. The complex cation is a different conformational isomer to that found in the previously studied tetraphenylborate salt. In the latter, Ag-N are 2.422(9) (central), 2.613(9), 2.399(7) Å (distal), with Ag-S 2.670(3) (central), 2.655(3), 2.949(4) Å (distal).